(untitled) (Research, Society and Development, 2024)
Introduction: The act of identifying oneself as an LGBTQIAP+ person is still understood as a transgression of heteronormativity, because heterosexuality is socially conceived as natural, while divergent sexualities are considered abnormal. Thus, it is inferred that the actor assuming LGBTQIAP+ generates occupational repercussions in the most diverse areas. Objective: the study aimed to identify, through a literature review, what are the occupational repercussions arising after coming out as an LGBTQIAP+ person and what impacts are caused in their lives. Method: The study is characterized as a literature review. The research was mediated by Health Sciences Descriptors (DeCS). Studies published in the last 5 years that dealt with the LGBTQIAP+ population were selected. Results: Of 206 articles, 13 were selected. From the analysis of the articles, it was identified that the occupational repercussions on LGBTQIAP+ individuals after coming out are related to work, psychosocial health, accessibility and assurance of civil rights. Conclusion: The LGBTQIAP+ population is still the target of various prejudices and stigmas, which commonly generate occupational injustices. The act of recognizing and assuming LGBTQIAP+ affects a wide spectrum of occupations, mostly in a negative way. However, it is essential to carry out more studies on the care of this population, so that improvements can be made in existing public policies, guaranteeing greater safety and quality of life.